Role of Photo-Biomodulation Therapy in Facial Rejuvenation and Facial Plastic Surgery - De Cordova, Jose A. (Facial Plastic Surgery, 2021)
Photo-biomodulation (PBM) also known as low-level laser therapy is a rising technology with multiple potential uses in medicine and recently in the cosmetic field for the treatment of skin conditions and skin rejuvenation. Due to its wound healing and anti-inflammatory properties, there is an increase in popularity in its use as adjunctive treatment before and after surgical procedures in the face and neck.
Keywords: photo-biomodulation; low-level laser therapy; light therapy